1984
DOI: 10.1002/j.1460-2075.1984.tb01764.x
|View full text |Cite
|
Sign up to set email alerts
|

Replication functions of pC194 are necessary for efficient plasmid transduction by M13 phage.

Abstract: Escherichia coli plasmids pBR313 and pBR322 were transduced by phage M13 with low efficiency (10(‐8) transductants/phage). Hybrid plasmids pHV12 or pHV33, composed of Staphylococcus aureus plasmid pC194 and pBR313 or pBR322, respectively, were transduced much more efficiently (10(‐4) transductants/phage). Inactivation of either of the two zones necessary for pC194 replication, one coding for a protein, the other not, reduced the transforming efficiency of hybrids to the level of pBR322. Activity of the pC194 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 37 publications
(19 reference statements)
0
34
0
Order By: Relevance
“…Of the three other plasmids from S. aureus that have been completely sequenced, both pC194 and pE194 contain open reading frames potentially coding polypeptides other than those responsible for antibiotic resistance Weisblum, 1982a, 1982b;Dagert et al, 1984). Furthermore, regions indispensable for replication have been identified on both plasmids and show striking similarities in their structural elements: a short G-C rich inverted complementary repeat (12-14 bp) adjacent to a longer inverted complementary repeat sequence (106-124 bp).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the three other plasmids from S. aureus that have been completely sequenced, both pC194 and pE194 contain open reading frames potentially coding polypeptides other than those responsible for antibiotic resistance Weisblum, 1982a, 1982b;Dagert et al, 1984). Furthermore, regions indispensable for replication have been identified on both plasmids and show striking similarities in their structural elements: a short G-C rich inverted complementary repeat (12-14 bp) adjacent to a longer inverted complementary repeat sequence (106-124 bp).…”
Section: Resultsmentioning
confidence: 99%
“…A high-copy number mutant, cop-6, of pE194 was attributed to a single base change (G to A) which mapped -100 bp from the shorter inverted complementary repeat. Although studies by Goze and Ehrlich (1980), and by Horinouchi and Weisblum (1982a) suggested that pE194-encoded polypeptides were unlikely to be required for replication, there is ample evidence to implicate a plasmid-specified protein in the replication of pC194 (Iordanescu and Surdeanu, 1983;Dagert et al, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Standard transformation techniques were used in all cases. Plasmids pUC19 (41), pC194 (6,19), and pUB110 (25) have all been sequenced; the published nucleotide numbering has been maintained in this work (pC194 as described in reference 6). Plasmid pHV1160 was derived from pHV653 (26), by inserting a polylinker present in pGC2 (28) Fig.…”
mentioning
confidence: 99%
“…Although in other experiments [12] insertion ofpBR322 DNAin the same HpuII site of pC 194 did not entail a loss of autonomous replication, both the transforming activity and the copy number of this hybrid plasmid were decreased. These experiments can hardly be compared to those reported in the present work.…”
Section: Discussionmentioning
confidence: 65%